Machiavelli in tumult the Discourses on Livy and the Origins of political conflictualism - Pedullà, Gabriele 1972- (Cambridge University Press, 2018)
Among the theses that for centuries have ensured Niccolò Machiavelli an ambiguous fame, a special place goes to his extremely positive opinion of social conflicts, and, more in particular, to the claim that in ancient Rome 'the disunion between the plebs and the Roman senate made that republic free and powerful' (Discourses on Livy I.4). Contrary to a long tradition that had always highly valued civic concord, Machiavelli thought that - at least under certain conditions - internecine discord could be a source of strength and not of weakness, and built upon this daring proposition an original vision of political order. Machiavelli in Tumult (originally published in Italian in 2011) is the first book-length study entirely devoted to analyzing this idea, its ancient roots (never before identified), its enduring (but often invisible) influence up until the American and the French Revolution (and beyond), and its relevance for contemporary political theory
Title from publisher's bibliographic system (viewed on 30 Aug 2018)
Concordia parvae res crescunt : the humanistic backdrop -- a necessary inconvenience : the demystification of political concord -- From philosophy to history -- Relishing the savor vs. hearing -- Battles over chronologies -- Tumults, tribunes and mixed government -- Tumults and humors -- The modes of tumults -- Between friends and enemies -- The aims of tumults -- Fear and virtue : the rebuttal to humanistic pedagogy -- A precarious freedom -- The fragility of virtuousness -- Terror : the greatest master there is -- The many faces of fear -- The empty throne -- the guard of liberty : the rejection of Aristotelian balance -- Checks without balance -- Two or three? -- A skeptical populism -- Giving the foreigners citizenship : an expansionist republicanism -- A humanistic theory of citizenship? -- The Roman model -- The Aristotelian model -- Conquest or concord? -- Reviving Roman expansionism -- Dionysius' reappearance : the classical roots of modern conflictualism -- In the footsteps of Polybius? -- Dionysius: mixed government and roman tumults -- Dionysius : dictatorship and Roman tumults -- Dionysius : citizenship and Roman tumults -- Dionysius and/or Livy -- Remembering the conflict : Machiavelli's legacy -- Between Aristotle and Hobbes -- A third paradigm (1531-1789) -- Conflict remembered (1789-2000) -- Machiavelli and us
Keywords: Machiavelli, Niccolò / 1469-1527 / Discorsi sopra la prima deca di Tito Livio; Livy / Ab urbe condita; Machiavelli, Niccolò -- 1469-1527 -- Discorsi sopra la prima deca di Tito Livio; Political science / Early works to 1800; Politischer Konflikt -- Motiv